Evolution of the number and size of the inclusions during steel treatment in a ladle furnace and in a vacuum caisson - Adolf, Zdeněk (Materiali in tehnologije, 2012)
The production of higher steel grades, such as steel for pipelines, requires monitoring the content of inclusions in the steel. Hence, the steelmakers have to choose suitable technological procedures that ensure the highest purity of the steel. Purpose of this work was to observe the evolution of the inclusions in the steel during its refining in a ladle furnace and in a vacuum caisson. For this purpose the samples of steel were taken at various stages of the processing. In one half of the melts the steel was deoxidised by CaSi-cored wire in a ladle furnace so that it would be possible to observe the influence of the CaSi on the occurrence of inclusions after degassing in the caisson. All the heats were processed in the following technological flow: OBM converter - ladle furnace - vacuum caisson (ISSM) - continuous casting.
Keywords: jeklo; steel; vključki; inclusions; modification; modifikacije; calcium; kalcij